Contribution of hypertension and other risk factors to survival and mortality in the Russian population - Yu. A. Balanova (Кардиоваскулярная терапия и профилактика, 2021)
Aim. To study the contribution of hypertension (HTN) to survival and mortality in the Russian population.Material and methods. This prospective observational cohort included representative samples from 11 Russian regions (men and women aged 25-64 years, n=18251) examined in 2012-2014 as part of the Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation (ESSE-RF) study. The examination included a questionnaire (12 modules), anthropometric and blood pressure (BP) measurements, as well as biochemical blood tests. HTN was considered aa a systolic BP ≥140 mm Hg and/or diastolic BP ≥90 mm Hg, or when a subject receives antihypertensives. Treatment efficacy was considered as the proportion of persons (%) who achieved target BP among those taking antihypertensives. Depending on HTN status, all participants were divided into 4 groups: 1) those without HTN;2)        those with HTN, taking antihypertensive agents and having systolic BP ≤140 mm H. and diastolic BP ≤90 mm Hg (effective therapy);3)        those with HTN, taking medications, but not achieving target BP (ineffective therapy); 4) those with HTN, not taking antihypertensives. The life status of participants was updated every 2 years. Kaplan-Meier survival curves, as well as univariate and multivariate Cox proportional hazards models were created.Results. The presence of HTN significantly reduced survival (p<0,001) in the cohort, which is significant when adjusted for age (men — relative risk (RR)=1,47, p<0,001, women — RR=1,17, p<0,001). In the multivariate model, the male sex (RR=2,3 p<0,001), age increase, smoking, tachycardia, and HTN are significant for all-cause mortality only for men, but not for women. However, for women, absence of higher education was significant. The presence of HTN significantly worsens cardiovascular survival in both sexes (p<0,0001). HTN increases the risk of a composite endpoint for both men and women (p<0,001). Analysis of Kaplan-Meier curves showed the worst survival rate in persons with HTN, taking antihypertensive drugs, but not reaching target BP levels.Conclusion. The presence of HTN significantly worsens the survival rate of men and women. Special attention of medical community should be directed to increasing the proportion of effectively treated patients with HTN.